Чисельний розрахунок електричних полів при наявності криволінійної границі розділу між провідним та непровідним середовищами - Сокол, Є.І.; Резинкіна, М.М.; Сосіна, О.В.; Гриб, О.Г. (Електротехніка і електромеханіка, 2016)
Описано принципи врахування криволінійних границь розділу при використанні методу скінченних об’ємів для розрахунку посилення електричного поля на вершинах провідних стрижнів. За допомогою проведених розрахунків отримана
залежність максимальної напруженості електричного поля від висоти та радіуса округлення вершин стрижнів. У
результаті апроксимації даної залежності поліномом записано аналітичний вираз для напруженості зовнішнього
електричного поля, при прикладенні якого до провідного об'єкта певної висоти і радіуса округлення вершини на ньому
розвивається коронний розряд Описаны принципы учета криволинейных границ раздела при использовании метода конечных объемов для расчета
усиления электрического поля на вершинах проводящих стержней. С помощью проведенных расчетов получена зависимость максимальной напряженности электрического поля от высоты и радиуса скругления вершин стержней. В
результате аппроксимации данной зависимости полиномом записано аналитическое выражение для напряженности
внешнего электрического поля, при приложении которого к проводящему объекту определенной высоты и радиуса
скругления вершины на нем развивается коронный разряд. Purpose. To elaborate a method of electric field numerical calculation in systems with curved boundaries between conductive
and non-conductive mediums at final volume method usage and
application of the rectangular grids. Methodology. At electric
field calculation in quasi-stationary approximation, potential of
the whole conductive object (rod) is constant. At final difference
scheme writing, presence of the curved part of the boundary
between conducting and non-conducting media has been taking
into account as follows. It was supposed that curved section
complements the closed loop on which integration of the solvable equation is done instead of a straight section which extends
within a conducting medium. Usage of this approach allows
taking into account square of the curved sections of the boundary and distance between surface of non-conductive medium
and nearest nodes of the computational grid. Results. Dependence of the maximum electric field intensity on the height and
radius of curvature peaks rods has been got with the help of
calculations. As a result, a polynomial approximation for the
analytical expression of the external electric field intensity,
upon which application to the conductive object of a certain
height and radius of curvature of its top, corona discharges will
develop